Factors Associated With Initiating Breastfeeding and Continuing it for At Least 4 Months in Consuelo, a Rural Town in the Dominican Republic - Anjalee Bhuyan BA; Anabel Fernandez MPH; Jennifer A. Faerber PhD; Ingrid Japa MD, MPH; Angie Alvarez MD; Ramona Cordero RN; Ivelisse Tavarez RN; Nahara Saballos MD, MPH; Andrew P. Steenhoff MBBCh, DCH (SAGE Publishing, 2023)
Objective . We assessed the proportion of and factors associated with mothers initiating and continuing breastfeeding (BF) for ≥4 months in a rural town of the Dominican Republic. Methods. A survey was administered to 190 mothers of children cared for at a free clinic in Consuelo. Modified bivariate and multivariable Poisson regressions were utilized in data analysis. Results. BF was initiated in 89.5% of cases and continued ≥4 months in 81.7% of cases. Maternal education beyond secondary school [adjusted RR = 1.13, 95% CI: (1.04-1.24), 0.010], and visiting both public and private antenatal clinics [adjusted RR = 1.25; 95% CI: (1.10-1.37), 0.010] were associated with BF initiation. Public and private antenatal clinic attendance [adjusted RR = 1.01, 95% CI: (0.45-2.23), 0.020], Cesarean section [adjusted RR = 0.81, 95% CI: (0.68-0.98), 0.026], number of biological children [adjusted RR = 0.95, 95% CI: (0.90-1.00), 0.032] and maternal employment [adjusted RR = 0.89, 95% CI: (0.79-0.99), 0.048] were associated with BF continuation. Conclusions. These results provide valuable insights for targeting specific populations in future breastfeeding education interventions.